As práticas educativas familiares no processo de distinção geracional criança/adulto (Caetité-BA, 1910-1930) - Giane Araujo Pimentel Carneiro (2011)
This study aimed to examine the family educational practices experienced by children in Caetité-BA in order to understand how the generational distinction happened among child/adult in the period between the 1910s and 1930s. In these first decades of the twentieth century children played a speech role in the republican project speeches to ensure the progress and future of the country it would be up to the older generation to educate the child. In these educational activities experienced by children in the family were differences produced between the condition of being child and the condition of being adult? To enter the private family daily lives and investigate this question, we had enjoyed the exchanged mails among the members of a local elite family, the numerous preserved family albums photographs and two memoirs books of people who lived their childhood in Caetité at the time of the study. The data intersection still was possible through the news from the newspaper A Penna, published in the city and with effective circulation in those days as well as documents from other institutions the effective activities practiced since birth, initially for life and health maintenance, showed that generational differences were produced to enhance the child weakness and subordination condition in relation to adults and among other children themselves, depending on age, gender, color and the family economic status. It was also possible to notice the distinctions between child/adult in the effectiveness of early training as walking, talking, playing, praying until the acquisition required skills in reading and writing practices. Despite the child broad participation with some autonomy in these processes sometimes imitating adult life others experiencing a specific universe produced for childhood, we found that there was an adult/child generational distinction process going on and that much effort was undertaken in preparation to adulthood especially among elite children families.